Transient expression of small secreted proteins of colletotrichum falcatum elicits broad-spectrum disease resistance in tobacco - Amalamol, Dharmaraj; Ashwin, N. M. R.; Lakshana, Kana Valiyaveettil; Ramesh Sundar, Amalraj; Jeevalatha, A.; Ramesh, R.; Malathi, P.; Viswanathan, R. (Plant Cell Reports, 2026)
Small secreted proteins (SSPs) play crucial roles in pathogenicity and host manipulation. C. falcatum, the causative agent of red rot in sugarcane, secretes numerous SSPs during its interaction with the host. In this study, three abundantly secreted SSPs of C. falcatum-CfEPL1 (eliciting plant response-like protein 1), CfPDIP1 (plant defence inducing protein 1), and CfBYS1 (Blastomyces yeast phase-specific protein 1) were transiently expressed in the model system, Nicotiana tabacum, to delineate their functional roles. Upon co-expression with green fluorescent protein (GFP), fluorescence signals of all three SSPs were predominant in the apoplastic spaces, consistent with the localisation predictions. Among the three SSPs, transient expression of CfEPL1 and CfPDIP1 induced a hypersensitivity response (HR), reactive oxygen species (ROS) production, and callose deposition in the infiltrated regions. However, transient expression of CfBYS1 triggered neither visible HR nor prominent upregulation of defence-related genes. Transcription profiling of defence-related genes in N. tabacum leaves infiltrated with CfEPL1 and CfPDIP1 indicated an upregulation of various genes associated with systemic acquired resistance (SAR), salicylic acid (SA), and jasmonic acid (JA) pathways. Inoculation of Pseudomonas syringae pv. tomato DC3000 (Pto) at the site of CfEPL1 and CfPDIP1 infiltration resulted in attenuated disease lesion development. Similarly, a reduction in bacterial wilt disease severity was observed, when the vacuum-infiltrated tobacco plants were challenged with Ralstonia solanacearum, which was substantiated by pathogen biomass quantification and SAR-associated marker expression profiling. Overall, this study demonstrated that the two SSPs, CfEPL1 and CfPDIP1, could confer broad-spectrum disease resistance in N. tabacum. [GRAPHICS]
Keywords: PAMP; Small secreted proteins; systemic acquired resistance; Transient expression